Incidental discovery of endourethral clip migration 10 years after radical prostatectomy: A case report and review of the literature. Issue 1 (February 2022) - Symeonidis, Evangelos N; Memmos, Dimitrios; Langas, Georgios; Bouchalakis, Athanasios; Baniotis, Panagiotis; Savvides, Eliophotos; Stefanidis, Panagiotis; Mutomba, Wilbert F; Dimitriadis, Georgios
Introduction: Surgical clips (SCs) have been widely used for a variety of surgical procedures over the years. Despite their advantages and proven effectiveness, several clip-related complications have been reported, creating dilemmas as to their optimal use. Case description: Herein, we present a rare delayed and incidental discovery of two endourethral metallic SCs in a 77-year-old male seeking treatment for acute renal colic. The patient had undergone open radical retropubic prostatectomy 10 years ago, and had an uneventful postoperative recovery. Computed tomography scan revealed left-sided hydronephrosis secondary to proximal ureteral calculus, as well as SCs at the level of vesico-urethral (VUR) anastomosis. Flexible cystoscopy confirmed the imaging findings, showing two endourethral clips, partly obstructing the VUR. Firstly, a serial wire-guided dilation took place, followed by left ureteral double-J stent placement. Unfortunately, the clips could not be concurrently removed due to their firm attachment to the bladder neck. Hence, our patient was scheduled for transurethral resection of the bladder neck and simultaneous endoscopic clip removal. Conclusions: To the best of our knowledge, this is the first report to highlight such a delayed incidental finding, 10 years after open retropubic radical prostatectomy (RRP), during a JJ stent insertion for obstructive uropathy without previous clip-induced lower urinary tract symptoms. Although rare, physicians should be aware of the potential clip-related complications arising either in the short- or long-term postprostatectomy setting.